2017
DOI: 10.1002/2016gl072325
|View full text |Cite
|
Sign up to set email alerts
|

Observation and interpretation of energetic ion conics in Jupiter's polar magnetosphere

Abstract: NASA's Juno spacecraft successfully completed its first science polar pass over Jupiter's northern and southern aurora, with all the instruments powered, on 27 August 2016. Observations of conical energetic proton distributions at low altitudes (<6 RJ) over the northern polar region are interpreted as resulting from transversely (to the local magnetic field lines) accelerated H+ at a position planetward of the point of observation. The proton conics were observed within a broad region of upward beaming electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 22 publications
4
44
0
Order By: Relevance
“…These energies are consistent with findings by Mitchell et al (2009) and similar to those found at Jupiter (e.g., Clark et al, 2017aClark et al, , 2017b but about a hundred times more energetic than at Earth (e.g., Gorney et al, 1985). These energies are consistent with findings by Mitchell et al (2009) and similar to those found at Jupiter (e.g., Clark et al, 2017aClark et al, , 2017b but about a hundred times more energetic than at Earth (e.g., Gorney et al, 1985).…”
Section: Conclusion and Summarysupporting
confidence: 89%
“…These energies are consistent with findings by Mitchell et al (2009) and similar to those found at Jupiter (e.g., Clark et al, 2017aClark et al, , 2017b but about a hundred times more energetic than at Earth (e.g., Gorney et al, 1985). These energies are consistent with findings by Mitchell et al (2009) and similar to those found at Jupiter (e.g., Clark et al, 2017aClark et al, , 2017b but about a hundred times more energetic than at Earth (e.g., Gorney et al, 1985).…”
Section: Conclusion and Summarysupporting
confidence: 89%
“…The previous work discussed earlier focused on ions with incident energies between 1 and 2 MeV/u, as these high ion energies are responsible for X‐ray emissions. However, we now know that ions with a wide range of energies precipitate into the polar cap, as confirmed by National Aeronautics and Space Administration (NASA)'s Juno spacecraft (Clark, Mauk, Haggerty, et al, ; Clark, Mauk, Paranicas, et al, ; Connerney et al, ; Haggerty et al, ; Szalay et al, ). Hence, we now model a much broader range of incident ion energies than previously considered (i.e., from 10 keV/u to 5 MeV/u).…”
Section: Physical Processes and Model Descriptionmentioning
confidence: 95%
“…As mentioned previously, there are several types of energetic electron distributions associated with the main aurora. Previous publications have focused on two general types: broadband with no peak and the peaked distributions (Allegrini et al, ; Clark, Mauk, Paranicas, et al, ; Ebert et al, ; Mauk et al, , , ). Here we expand the list and show the various types of electron distributions (Figure ) associated with the main auroral crossings.…”
Section: Energetic Electron Observationsmentioning
confidence: 99%